Integrative Review of Dietary Choice Revealed by fMRI: Considerations for Obesity Prevention and Weight-Loss Education - Long, JoAnn D. (2020)
Background Emerging findings from neuroimaging studies investigating brain activity associated with dietary behavior are illuminating the interaction of biological and behavioral mechanisms that have implications for obesity prevention. Globally, A total of 1.9 billion adults are overweight, and 650 million are obese. Obesity and being overweight are major risk factors for chronic illness and death. Behaviorally based health interventions have had limited success in curbing the obesity epidemic. Greater understanding of brain responses to food cues will contribute to new knowledge and shape public health efforts in obesity prevention. However, an integration of this knowledge for obesity prevention education has not been published. Aims This study links evidence generated from brain activation studies generated in response to diet and food images and highlights educational recommendations for nurses engaged in obesity prevention and weight-loss education. Methods An integrative review of the literature was conducted using the MeSH keywords “magnetic resonance imaging,” “diet,” and “food images” in PubMed, MEDLINE Complete, CINAHL, and Cochrane databases from their first appearance in 2006 through March 2018. Studies published in English and using functional magnetic resonance imaging to measure brain response to diet, and food images were initially identified. Animal models, those whose primary focus was a specific disease, and intervention studies were excluded. Results Of 159 studies identified, 26 met inclusion criteria. Findings from neuroimaging studies may help explain the relationship between brain mechanisms and behavioral aspects of dietary choice and inform patient education in obesity prevention. Awareness of this evidence is applicable to nursing education efforts. This review contributes several recommendations that should be considered by nurses providing individualized weight-loss education. Linking Evidence to Action Nurses engaged in patient education for obesity prevention should consider personalized interventions that cultivate internal awareness for dietary adherence, self-care, exercise, hydration, and mood state; avoid using caloric deprivation approaches, such as skipping breakfast, for weight-loss interventions; and note the importance of individualized obesity prevention and weight-loss education.